The role of effective communication and trustworthiness in determining guests' loyalty. Issue 2 (17th February 2019) - Kharouf, Husni; Sekhon, Harjit; Fazal-e-Hasan, Syed Muhammad; Hickman, Ellie; Mortimer, Gary
ABSTRACT: This study investigates the role of trustworthiness and effective communication in the development of guests' loyalty within the hotel sector. We propose and test a conceptual model that differentiates between two types of loyalty: attitudinal and behavioral. As hotels can control and manage how they communicate their desired characteristics to guests, we posit effective communication and a hotel's trustworthiness as the key concepts in building loyalty. This study reports on the findings of a study based on 322 hotel guests. Data were analyzed using structural equation modeling. The results reveal that implementing effective communication methods leads to a trustworthy image, which in turn has a positive impact on attitudinal and behavioral loyalty. This research provides hotel managers with strategic directions for cultivating guest loyalty.